Prevalence and Correlates of Multiple Cardiovascular Risk Factors in Children with Chronic Kidney Disease - Wilson, Amy C. (American Society of Nephrology, 2011)
SUMMARY: BACKGROUND AND OBJECTIVES: Although prevalence of traditional cardiovascular risk factors (CVRF) has been described in children with CKD, the frequency with which these CVRF occur concomitantly and the clinical characteristics associated with multiple CVRF are unknown. This study determined the prevalence and characteristics of multiple CVRF in children in the Chronic Kidney Disease in Children study. DESIGN, SETTING, PARTICIPANTS, & MEASUREMENTS: Using cross-sectional data from first follow-up visits, we determined the prevalence of four CVRF: hypertension (casual BP >95(th) percentile or self-reported hypertension with concurrent use of anti-hypertensive medication), dyslipidemia (triglycerides >130 mg/dl, HDL <40 mg/dl, non-HDL >160 mg/dl, or use of lipid-lowering medication), obesity (BMI >95(th) percentile), and abnormal glucose metabolism (fasting glucose >110 mg/dl, insulin >20 μIU/ml, or HOMA-IR >2.20, >3.61, or >3.64 for those at Tanner stage 1, 2 to 3, or 4 to 5, respectively) in 250 children (median age 12.2 years, 74% Caucasian, median iohexol-based GFR 45.2 ml/min per 1.73 m(2)). RESULTS: Forty-six percent had hypertension, 44% had dyslipidemia, 15% were obese, and 21% had abnormal glucose metabolism. Thirty-nine percent, 22%, and 13% had one, two, and three or more CVRF, respectively. In multivariate ordinal logistic regression analysis, glomerular disease and nephrotic-range proteinuria were associated with 1.96 (95% confidence interval, 1.04 to 3.72) and 2.04 (95% confidence interval, 0.94 to 4.43) higher odds of having more CVRF, respectively. CONCLUSIONS: We found high prevalence of multiple CVRF in children with mild to moderate CKD. Children with glomerular disease may be at higher risk for future cardiovascular events.